Menilai Ulang Gagasan Negara Khilâfah Abû Al-A’lâ Al-Maudûdî - Arsyad Sobby Kesuma Sobby Kesuma (Universitas Islam Negeri Mataram, 2008)
In the midst of unstable democracy system, the idea about Islamic state or khilâfah, referring to some Muslim thinkers’ views, begins to get fresh wind. This writing presents al-Maududi’s view on Islamic state and khilâfah system centered in theo-democracy that is still unclear how to be implemented in the real practice especially in our situation now. Substantially, his basic ideas are acceptable, for example his thought of goals and functions of state establishment. However, his view that only men are eligible to be ‘amîr is difficult to accept for public today. Al-Maududi is one of Muslim scholars who is persevering in establishing an Islamic state based on al-Qur’an and Hadist. Basically, al-Maududi agrees any state form. However, he emphasizes the significance of theo-democracy state model as a characteristic of an Islamic state that is different from republic system that applies democracy in the West.